Pengembangan Program Studi Keahlian pada SMK Sesuai Kegiatan Ekonomi Utama di Enam Koridor Ekonomi - Siswantari – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2015)
The purpose of this study was to analyze the expertise study programs that need to be held in vocational secondary school and to find the development pattern of expertise competency in provincial level and/or expertise study program and expertise competency in the district/city level appropriate with its main economic activities. The study used survey and discussion method. The study used primary and secondary data. Primary data was the expertise study program needed to develop 20 main economic activities, collected by discussion with association in Main Economic Activities. Secondary data was the expertise study program conducted in 13 sample provinces, collected using questionnaires with respondent of the head of secondary education division in provincial education offices. The study showed that all provinces needed to open study programs to develop 20 main economic activities. This study concluded that expertise study program conducted in the provinces were not appropriate with its Main Economic Activities. Analysis in this study can be applied to consider opening expertise competency in the provincial level and/or expertise study program and expertise competency in district/city level. ABSTRAKTujuan studi ini yaitu menganalisis program studi keahlian di sekolah menengah kejuruan yang perlu diselenggarakan dan menemukan pola pengembangan kompetensi keahlian di tingkat provinsi serta program studi keahlian dan kompetensi keahlian untuk tingkat kabupaten/kota yang sesuai dengan kegiatan ekonomi utama. Studi ini menggunakan metode survei dan diskusi. Data yang digunakan yaitu data primer dan sekunder. Pengumpulan data primer bersumber dari program studi keahlian untuk pengembangan 20 kegiatan ekonomi utama yang dilakukan melalui diskusi dengan asosiasi bidang kegiatan ekonomi utama. Data sekunder berupa program studi keahlian yang diselenggarakan di 13 provinsi sampel dikumpulkan melalui angket terhadap kepala bidang pendidikan menengah dinas pendidikan provinsi. Hasil studi memperlihatkan semua provinsi sampel perlu membuka program studi keahlian yang sesuai untuk pengembangan 20 kegiatan ekonomi utama. Kajian ini menyimpulkan program studi keahlian yang diselenggarakan belum sesuai dengan kebutuhan kegiatan ekonomi utama masing-masing provinsi. Analisis kajian ini dapat diterapkan untuk pertimbangan membuka kompetensi keahlian di tingkat provinsi dan/atau membuka program studi keahlian dan kompetensi keahlian di tingkat kabupaten/kota.